Bioslurry as a Fuel. 3. Fuel and Rheological Properties of Bioslurry Prepared from the Bio-oil and Biochar of Mallee Biomass Fast Pyrolysis - Abdullah, Hanisom; Mourant, Daniel; Li, Chun-Zhu; Wu, Hongwei (American Chemical Society, 2010)
This study investigates fuel and rheological properties of bio-oil/char slurry (i.e., bioslurry) fuels, which were prepared by mixing bio-oil with different concentrations of biochar. The bio-oil and biochar were produced from mallee fast pyrolysis at 500 °C. The excellent grindability of biochar enables desirable particle size reduction of biochar into fine particles, which can be suspended into bio-oil for the preparation of bioslurry fuels. The bioslurry fuels have desired fuel and rheological characteristics, which meet the requirements for combustion and gasification applications. Dependent upon biochar loading, the volumetric energy density of bioslurry is up to 23.2 GJ/m3, achieving a significant energy densification (by a factor >4) in comparison to green wood chips.Bioslurry fuels with high biochar concentrations (11−20 wt %) show non-Newtonian characteristics with pseudo-plastic behavior. The flow behavior index, n, decreases with an increasing biochar concentration. Bioslurry with higher biochar concentrations also demonstrate thixotropic behavior. The bioslurry fuels also have low viscosity (<453 mPa s) and are pumpable at both room and elevated temperatures. The concentrations of Ca, K, N, and S in bioslurry are below the limits of slurry fuel guidelines. Overall, the results in this study suggest that bioslurry fuels achieve substantial volumetric energy densification and are suitable fuels for combustion and gasification applications.